New Imaging Method of Mobile Phone-Based Colorimetric Sensor for Iron Quantification - Ngan Anh Nguyen; Asher Hendricks; Emily Montoya; Amber Mayers; Diwitha Rajmohan; Aoife Morrin; Margaret McCaul; Nicholas Dunne; Noel O’Connor; Andreas Spanias; Gregory Raupp; Erica Forzani (Sensors)
Blood iron levels are related to many health conditions, affecting hundreds of millions of individuals worldwide. To aid in the prevention and treatment of iron-related disorders, previous research has developed a low-cost, accurate, point-of-care method for measuring iron from a single finger-prick blood sample. This study builds upon that work by introducing an improved imaging method that accurately reads sensor images irrespective of variations in environmental illumination and camera quality. Smartphone cameras were used as analytical tools, demonstrating an average coefficient of variation of 5.13% across different phone models, and absorbance results were found to be improved by 8.80% compared to the method in a previous study. The proposed method successfully enhances iron detection accuracy under diverse lighting conditions, paving the way for smartphone-based sensing of other colorimetric reactions involving various analytes.